Invasive Egg Predators and Food Availability Interactively Affect Maternal Investment in Egg Chemical Defense - Paul, Sarah C.; Stevens, Martin; Burton, Jake; Pell, Judith K.; Birkett, Michael A.; Blount, Jonathan D. (Frontiers in Ecology and Evolution, 2018)
Invasive species commonly predate the offspring of native species and eggs are the life stage most vulnerable to this predation. In many species with no maternal care, females can alter the phenotype of eggs to protect them, for instance through chemical defence. In ladybirds egg alkaloids deter predators, including invasive predatory species of ladybirds, but conversely may attract cannibals who benefit from the consumption of eggs with higher alkaloid levels. Invasive predators tend to be more abundant where resources are also abundant, but in high resource environments the maternal fitness benefits of sibling cannibalism are low. Consequently this presents a conflict for female ladybirds between the different factors that influence egg alkaloid level, as protecting her eggs from predators might come with the cost of inadvertently encouraging within-clutch cannibalism under circumstances where it is not beneficial. We investigated how the ladybird Adalia bipunctata addresses this trade-off experimentally, by measuring the quantity of alkaloids in eggs laid by ladybirds in environments that differed in levels of resource availability and perceived predation risk from an invasive predator Harmonia axyridis. Females did lay eggs with higher egg alkaloid levels under poor resource conditions, but only when predator cues were absent. The resulting negative correlation between egg number and egg alkaloid level under poor resource conditions indicates a trade-off between these two attributes of maternal investment, mediated by female response to offspring predation risk. This implies that selection pressures on mothers to adaptively adjust the risk of siblicide may outweigh the need to protect offspring from interspecific predation. Our results demonstrate that maternal effects are an important aspect of species’ responses to invasive predators, and highlight the value of studying maternal effects in the context of the multifaceted environments in which they occur.